INDEKS PENCEMARAN PERAIRAN PESISIR MADONG KOTA TANJUNGPINANG - Tengku Said Razai; Imam Pangestiansyah; Nofrizal; Ramses (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2019)
Various activities in coastal areas have negative impacts on the ecological stability of the waters. The result of human anthropogenic activities around the water causes changes and degradation of the aquatic environment. The population development in the Tanjungpinang City area continues to increase and is starting to spread to the coastal area, one of which is the Madong coastal area. The Madong area is used for various kinds of coastal activities, including catching biota, transportation areas, fish ponds or cages for consumption, and residential areas. Thus, this area is prone to water pollution and a decrease in water conditions. For this reason, a recent study is needed related to the condition of water pollution which is described using the Water Pollutant Index. The results of the study show that the parameters of temperature, turbidity, DO, BOD, and pH are parameters that are still in accordance with the quality standard threshold in the Minister of Environment Decree No. 51 (2004). Meanwhile, the TSS value exceeds the water quality standard value, while the salinity is below the quality standard range because the location of Madong waters has a low salinity level. This condition is due to the fact that the waters of Madong are still influenced by freshwater rivers. Overall, the pollutant index value or the Pollutan index for Madong waters of 1.87 is classified as lightly polluted. however, an increase in activity in the future can worsen water conditions and have the potential to increase their pollutant value.